Regulatory Effectiveness : The Impact of Regulation and Regulatory Governance Arrangements on Electricity Industry Outcomes - Stern, Jon (World Bank, Washington, DC, 2012)
The authors review a number of studies on the effectiveness of utility regulatory agency and governance arrangements for the electricity industry, particularly for developing countries. They discuss governance criteria and their measurement, both legal frameworks and surveys of regulatory practice. They also discuss the results from econometric studies of effectiveness for regulatory agencies in the electricity and telecommunications industries and compare these with the results from econometric studies of independent central banks and their governance. The authors conclude with a discussion of policy implications and of priorities for information collection to improve understanding of these issues.